Graphene foam-embedded epoxy composites with significant thermal conductivity enhancement. Issue 38 (2nd July 2019) - Liu, Zhiduo; Chen, Yapeng; Li, Yifan; Dai, Wen; Yan, Qingwei; Alam, Fakhr E.; Du, Shiyu; Wang, Zhongwei; Nishimura, Kazuhito; Jiang, Nan; Lin, Cheng-Te; Yu, Jinhong
Abstract : A facile, low-cost and scalable method is developed to construct three-dimensional thermal transport channels like highways in polymer composites. Abstract : High thermal conductivity polymer composites at low filler loading are of considerable interest because of their wide range of applications. The construction of three-dimensional (3D) interconnected networks can offer a high-efficiency increase for the thermal conductivity of polymer composites. In this work, a facile and scalable method to prepare graphene foam (GF) via sacrificial commercial polyurethane (PU) sponge templates was developed. Highly thermally conductive composites were then prepared by impregnating epoxy resin into the GF structure. An ultrahigh thermal conductivity of 8.04 W m −1 K −1 was obtained at a low graphene loading of 6.8 wt%, which corresponds to a thermal conductivity enhancement of about 4473% compared to neat epoxy. This strategy provides a facile, low-cost and scalable method to construct a 3D filler network for high-performance composites with potential to be used in advanced electronic packaging.